STRENGTHENING OF REINFORCED CONCRETE SLAB WITH STEEL ELEMENTS (Collection of scientific works «Modern structures of metal and wood», 2025)
The need for inspection of building structures containing the fragment of the floor slab in the car park of a residential building arose due to appearance of damage. A fragment of the concrete floor slab was inspected, calculations for the slab were performed in accordance with the requirements of current regulatory documents, its technical condition was determined, and a conclusion was made concerning possibility for further operation. During the  research, a regulatory procedure  for  assessing the technical condition and load-bearing capacity of operated structures was applied. The results of performed survey, calculation and technical condition assessment for building structures containing the slab fragment were presented. It was determined that according to the current regulatory documents containing requirements for technical condition the concrete slab fragment is unusable for operation. The cause for defects and damage  in  the  slab  structure  was  determined:  violations  of  technology  for  execution  of  concrete structures in the winter. Based  on  the  research,  a  design  for  strengthening  the  slab  structure  was  developed. Manufacture, transportation and installation of steel reinforcing structures were carried out. Reinforcing the slab using the proposed method made it possible to complete the work in a short time without using wet processes. The load from the weight of the slab structures, according to  the develo
Keywords: existing building; fragment of concrete floor slab for car park; inspection; technical condition; design; manufacture and installation of reinforcing structures